2022
DOI: 10.3390/vaccines10030426
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mRNA COVID-19 Vaccination on SARS-CoV-2 Infection and COVID-19 in Sicily over an Eight-Month Period

Abstract: In order to reduce the spread of SARS-CoV-2 infection and the burden of disease, since 27 December 2020, Sicily has introduced a regional COVID-19 vaccination campaign. This study aimed at estimating the effectiveness of mRNA COVID-19 vaccines on SARS-CoV-2 infections and COVID-19. A retrospective cohort study was carried out on 3,966,976 Sicilian adults aged 18 years or more, who were followed-up from 1 January 2021 to 30 September 2021. The risk of SARS-CoV-2 infection, severe COVID-19, and COVID-19 death or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Similarly, a study carried out in the United Kingdom has reported a vaccine effectiveness of the booster dose of 73.9% against SARS-CoV-2 infection, consistent with our 78% [28]. However, the small variations in results between studies could be attributed to factors such as the prevalence of different COVID-19 variants, prevention strategies and population characteristics (e.g., mask-wearing was mandatory in Italy but not in the UK) [29,30]. In Israel, vaccine effectiveness against severe disease and death from COVID-19 was found to be 92% and 90%, respectively, confirming the soundness of our results against severe outcomes [31].…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, a study carried out in the United Kingdom has reported a vaccine effectiveness of the booster dose of 73.9% against SARS-CoV-2 infection, consistent with our 78% [28]. However, the small variations in results between studies could be attributed to factors such as the prevalence of different COVID-19 variants, prevention strategies and population characteristics (e.g., mask-wearing was mandatory in Italy but not in the UK) [29,30]. In Israel, vaccine effectiveness against severe disease and death from COVID-19 was found to be 92% and 90%, respectively, confirming the soundness of our results against severe outcomes [31].…”
Section: Discussionsupporting
confidence: 87%
“…Of the studies reporting in the UK, 14 were conducted specifically in England ( 10 , 13 , 14 , 24 , 42 , 49 , 50 , 53 ), 5 in Scotland ( 54 , 85 , 97 ), and 3 in Wales ( n = 3) ( 18 , 65 ). Other studies were in Israel ( n = 9) ( 15 , 29 , 30 , 39 41 , 57 , 74 , 92 ), Italy ( n = 8) ( 11 , 19 , 20 , 34 , 35 , 38 , 63 )), Brazil ( n = 6) ( 23 , 67 , 82 , 93 , 96 ), Malaysia ( n = 4) ( 44 , 76 , 77 ), Spain ( n = 4) ( 31 , 61 , 87 ), Finland ( n = 3) ( 68 , 87 ), South Africa ( n = 3) ( 67 , 82 , 98 ), Canada ( n = 3) ( 27 , 75 , 90 ), France ( n = 2) ( 62 ), Argentina ( n = 2) ( 67 , 82 ), Germany ( n = 2) ( 67 , 82 ), Qatar ( n = 2) ( 25 , 78 ), Sweden ( n = 2) ( 58 ), Hungary ( n = 2) ( 86 ), Turkey ( n = 2) ( 67 , 82 ), Kuwait ( n = 2) ( 8 ), South Korea ( n = 1) ( 47 ...…”
Section: Resultsmentioning
confidence: 99%
“…Twelve reviews were excluded from the 77 studies, 21 studies lacked sufficient data, two studies were related to inactivated vaccine, 58,59 and two studies were duplicated 24,60 . Finally, 40 studies out of total 1043 abstracts were finally included in our meta‐analysis, 16–54,60 involving 62 954 861 participates and two kinds of COVID‐19 mRNA vaccines, namely BNT162b2 and mRNA‐1273; two kinds of viral vector vaccines, namely ChAdOx1 and Ad26. COV2.S.…”
Section: Resultsmentioning
confidence: 99%